Humor dalam Video Animasi Green Burger pada Channel Youtube Egyptoon - KR, Mahfudz Siddiq (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2024)
Humor is an important asset possessed by humans. By having a good sense of humor, a person will be able to see, acknowledge, and accept reality as it is. In fact, humor can defuse difficult situations and reduce a person's stress levels. There are various ways that can be employed to cultivate humor, and one of them is through speech. This research aims to illustrate how humor situations are created in the animated video 'Green Burger' on the Egyptoon YouTube channel by violating the principles of cooperation in the speech found in the video, using Grice's cooperative principle theory through Juan Manser's theory of humor. The data source is the animated video 'Green Burger' on the Egyptoon YouTube channel, using a qualitative descriptive method. The results of the research indicate the presence of humor built through the violation of cooperative principles.